Caracterización de la cadena de abastecimiento de botellas de tereftalato de polietileno como estrategia de optimización del reciclaje en la ciudad de barranquilla (2015)
Nowadays bottles of polyethylene terephthalate (PET) are produced and consumed in large volumes by industry beverages and chemicals. After use these become a major contaminant materials on the planet. Every year around 500,000 billion bottles are manufactured in the world (EPA, 2012 cited by Meza, 2013). For this reason this project aims to devise a strategy based on the principles of reverse logistics that increase the rate of collection and recycling of PET bottles in Barranquilla, Colombia. Through literature research, review the state of the art and consultations in databases governmental and non-governmental, the current situation on the consumer, post-consumer PET characterization and pollution at national and local level is raised. According to the results of the research strategy based on reverse logistics concepts that can recover and reinstate the supply chain used PET bottles are raised. From these strategies can achieve volume reduction of pollutant materials Barranquilla.